How to Build Mathematical Abilities in Deaf Students? A Grounded Theory - Leton, Samuel Igo (Jurnal Pendidikan Progresif, 2022)
How to Build Mathematical Abilities in Deaf Students? A Grounded Theory. Objective: This study aims to produce a conceptual model as a strategy for building mathematical abilities in deaf students. Methods: This is qualitative research with a grounded theory design involving 45 deaf students from four middle schools in Indonesia. Findings: The results of the data analysis at the open coding stage obtained five categories of visual, feeling, understanding, learning experience, and habits in learning mathematics. At the axial coding stage, mathematical understanding was used as the core category. While at the selective coding stage, a conceptual model was built where each category contributes to building mathematical abilities. Conclusion: That efforts are crucial to develop the mathematical abilities of deaf students comprehensively. This can be done by visualizing the problems, connecting the problems with the student environment, providing learning experiences with various questions, giving motivation, and increasing self-confidence using praise and more attention from parents or teachers. Keywords: deaf student, grounded theory, mathematical abilities.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202240